THE INFLUENCE OF SOCIAL SUPPORT AND PSYCHOLOGICAL RESILIENCE ON STUDENTS’ EMOTIONAL INTELLIGENCE: THE MEDIATING ROLE OF SELF-EFFICACY - Thi Cam Tuyen, Trinh (HNUE Journal of Science: Journal of Educational Science, 2026)
This study aimed to examine the relationships among social support, psychological resilience, self-efficacy, and emotional intelligence among university students, while also testing the mediating role of self-efficacy. Data were collected from 613 students at universities in Ho Chi Minh City. The measurement scales were evaluated using Cronbach’s alpha, exploratory factor analysis (EFA), and confirmatory factor analysis (CFA). Results indicated that social support had a direct relationship with emotional intelligence (β = 0.212) and an indirect relationship through self-efficacy (β = 0.278), whereas psychological resilience was directly related to emotional intelligence (β = 0.187) and indirectly through self-efficacy (β = 0.255). The total effects suggest that self-efficacy partially mediates these relationships. Given the cross-sectional design, the findings only reflect associations and do not allow causal inferences. This study provides empirical evidence on the links between psychosocial resources and emotional intelligence among Vietnamese students, while also highlighting the potential mediating role of self-efficacy. The findings may inform psychological–educational support programs aimed at enhancing students’ emotional competencies.